KEANEKARAGAMAN JENIS KANTONG SEMAR (Nepenthes spp.) DI BERBAGAI KONDISI TUTUPAN HUTAN SEKUNDER DESA BUKIT BATU KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - Kristianus, .; Astiani, Dwi; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2018)
Nepenthes is one of plant species that found in Indonesian tropical forests. This plant has uniqueness and many benefits make this plant being hunted and exploited, caused the existence of its population are decreasing. Nepenthes inhabit in various conditions, one of the site is in lowland secondary forest. This study aims to find out site diversity of nepenthes in various secondary forest land cover conditions in Bukit Batu Village. This research is expected to be a baseline information on nepenthes diversity for the goal of protection and use fullness of nepenthes. This research employed survey method with purposive sampling on plot placement. Plot size was 20 m Ã— 20 m with sub plot was of 10 m Ã— 10 m. The results show that secondary forest of Bukit Batu Village which were varied on coverage condition, on open canopy 4 species of nepenthes were found such as N. ampullaria jack., N. bicalcarata Hook.F., N. rafflesiana Jack. and N. gracilis korth., under medium canopy coverage there was 3 nepenthes species found, which was N. ampullaria jack., N. bicalcarata Hook. F. and N. rafflesiana Jack., and under closed canopy conditions there was 2 species of nepenthes found N. ampullaria jack. and N. bicalcarata Hook. F. The results showed that only few nepenthes species found in this forest area and species nepenthes found more under open canopy condition, due to those species needed more light to survive.Keywords: Canopy Cover, Diversity, Nepenthes spp, Secondary Forest